Nurturing children through preschool and reception : developing the potential of every child - Peckham, Kathryn (London : Routledge, 2024)
The preschool and reception years can be viewed as a stage of preparation for formal schooling. But we must not lose sight of the profound impact this time of play and exploration has as children continue developing the core processes they will later rely on. Nurturing Children through Preschool and Reception explores how a child's mind and body develops during this critical and sensitive period and how the choices practitioners and parents make every day have a deep impact on these processes. Underpinned by the latest research in the fields of child development, psychology, health and well-being, it explores the practices that can be embedded straight away to support children's ongoing development and give them the best opportunities for future success. The book follows a holistic approach through the Nurturing Childhoods Pedagogical Framework and the ABCs of Developing Engagement, alongside methods to consider the impact of learning experiences, decoding children's evolving behaviours and strategies for their development. Chapters cover: Managing the expectations placed on the early years ; Connecting with children through communication, movement and play ; Recognising emotions and promoting effective choices ; Helping young children manage their emotions in a social world ; Developing young children's confidence to think and express themselves ; Understanding young children's friendships and conflicts ; Supporting lifelong learning in the years before school Part of the Nurturing Childhoods series, this exciting book provides practitioners and parentswith the knowledge and understanding they need to nurture children's happiness, well-being and sense of security through the preschool and reception years.
Section 1 Introduction1. Managing the expectations placed on Young Children2. Connecting with Young Children: Communication, Movement and Play3. Helping Young Children manage their emotions in a social world4. Supporting Young Children's developing behaviours5. Developing Young Children's confidence to think and express themselves6. Nurturing Young Children as they develop social skills7.Understanding Young Children's friendships8. Understanding the conflicts of Young Children9. Preparing for school10. Supporting lifelong learning in the years before schoolSection 2 Introduction: The Nurturing Childhoods Pedagogical Framework11. Nurturing Young Children to do things for themselves12. Nurturing Young Children to do new things13. Nurturing Young Children to be brave14. Nurturing Young Children to have good ideas15. Nurturing Young Children to have a go16. Nurturing Young Children to have fun17. Nurturing Young Children to think
"A David Fulton book."
Keywords: Preschool children; Education, Preschool; Child development; Child psychology; EDUCATION / Preschool & Kindergarten; EDUCATION / Elementary; EDUCATION / Professional Development